Modern buffets blueprint for success - Leonard, Edward G. (Wiley, 2012)
"The first new professional book published on this subject in years, Modern Buffets: Blueprint for Success by Edward Leonard, CMC, features the newest trends in buffet presentations and the story behind why one of America's favorite ways to eat is changing for the better. The text begins with a brief history of buffets in America and abroad, and proceeds into the new methods guaranteed to exceed customer expectations and set the standards for a whole new dining experience. Chapters include recipes and menu ideas, as well as numerous photos of buffets, centerpieces, plate presentations, dine around concepts, and action stations. Whether working in or studying about any aspect of the hospitality business the students will be sure to find a valuable resource in this new text"-- Provided by publisher.